Clinical characteristics of patients with P4HTM variant-associated epilepsy and therapeutic exploration: a case report and literature review - Wang, Yan-Juan; Li, Si-Xiu; Hu, Wen-Guang; Zhao, Li-Li; Lan, Mingping; Chen, Jia-Lei (Frontiers in Neurology, 2024)
The P4HTM gene encodes a transmembrane prolyl 4-hydroxylase, which is responsible for the degradation of hypoxia-inducible transcription factors (HIF) under normoxia. Clinically, biallelic P4HTM variants have been identified in patients with hypotonia, hypoventilation, intellectual disabilities, dysautonomia, epilepsy, and eye abnormalities (HIDEA syndrome). Seizure was one of the most prominent symptoms. However, the clinical features of patients with epilepsy associated with P4HTM variants remain unclear. In this report, we describe a one-month-old infant with HIDEA syndrome caused by compound heterozygous P4HTM variants (c.300dupG/p.Gly103Argfs*22 and c.488C > T/p.Ala163Val). The infant presented with clonic seizures of focal onset that responded well to valproate, but with profound intellectual disability and global developmental delay at the last follow-up at 3 years old. A review of the existing literature indicates that seizures in this population typically begin early in infancy, manifest in multiple types, and are relatively well controlled. Epilepsy seemed unrelated to developmental outcomes or disease progression. Valproate, which has HIF-1α inhibiting properties, may be a promising treatment avenue for this population.